Standardisation of indicators of quality of products cognitive technologies - Antsyferov, S.S. (Искусственный интеллект, 2014)
The standard set of quality indicators, reflecting the principal features of functioning and development of intellectual systems is proposed. Comparative assessment of some of them is given.